2006
DOI: 10.1007/s11249-006-9045-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical evaluation of friction at contacting magnetic storage slider–disk interfaces

Abstract: To understand better the friction force and wear processes at contacting slider-disk interfaces, we have developed an experimental method for measuring and a theoretical method for calculating the friction force. For this study, a slider with a 1500 lm 2 contact pad located at the recording head is burnished against a relatively rough disk ( $ 12 Å rms), which ensures smooth sliding. In the experimental method, the friction force is measured as the disk is spun-down to bring the slider-disk interface into an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
(42 reference statements)
0
18
1
Order By: Relevance
“…The presence of lubricant effectively decreases the net clearance between two rough surfaces by an amount t and, more significantly, results in smaller resistance to shear within lubricant contact. Hence, it can be said that the disk lubricant effectively reduces the strength of contact junctions as was found in experiments [6].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The presence of lubricant effectively decreases the net clearance between two rough surfaces by an amount t and, more significantly, results in smaller resistance to shear within lubricant contact. Hence, it can be said that the disk lubricant effectively reduces the strength of contact junctions as was found in experiments [6].…”
Section: Discussionmentioning
confidence: 63%
“…This model is coupled with an existing rough surface dynamic contact model with friction [3,4] that has been extended to include variable lubricant surface energy according to recent experimental measurements [5,6]. Customarily, MTL contact has been neglected in rough surface contact models by assuming that the lubricant is readily displaced upon contact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, as shown for example by McCool [9], allowing multi-scale roughness (different radii of curvature of asperities) does not significantly change the simpler results of the original GW model. Also, despite the known limitations of the GW model, researchers have shown that the GW-based contact model gives good correlation with experiments [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining good tribological properties such as low wear and stiction of such a high speed sliding interface at low clearance is critical for the long term reliability of hard disk drives [7]. Any contact between the head and the disk leads to friction and wear of the head overcoat layer, adversely impacting the disk drive performance [8][9][10][11].A unique way of reducing the friction during contact is through externally imposed oscillations of small amplitude and energy. Previous experimental and theoretical work to reduce the friction at a sliding interface explored the use of external excitation with either surface acoustic waves or electrostatic forces to modulate the out-of-plane or in-plane motion [12][13][14][15].…”
mentioning
confidence: 99%